Description of the Incidence of Anemia in Young Women at SMPN 2 Depok, Yogyakarta - Dani Ferdian; Rohman Hikmat; Yogi Lasril; Abdullah Anshor; Triyanto Triyanto (Sriwijaya Journal of Medicine, 2024)
Anemia is an important problem experienced by many teenagers. Anemia is a lack of red blood cells in the body. Young women are more susceptible to anemia, this is related to their own condition of experiencing menstruation (menstruation) and the result of an unhealthy diet. Therefore, further research is needed to describe anemia in adolescent girls. The aim of this study is to describe the incidence of anemia in adolescent girls at SMPN 2 Depok, Yogyakarta. The method used in this research is descriptive study. The sample in this study used total sampling. The sample was 57 8th grade teenage girls at SMPN 2 Depok, Yogyakarta. data analysis using descriptive analysis. As much as 56.14% of the 51 teenage girls who took part in the activity had anemia or anemia (32 teenage girls). This shows that the incidence of anemia among adolescent girls at SMPN 2 Depok is still high. One of the causes of anemia in adolescent girls is the lack of prevention of anemia in adolescent girls, such as taking blood supplement tablets and consuming foods with balanced nutrition. The incidence of anemia in adolescent girls is still high, so efforts are needed to prevent anemia by schools collaborating with nearby health facilities.